The role of CNVs in the etiology of rare autosomal recessive disorders: the example of TRAPPC9-associated intellectual disability. (January 2018) - Mortreux, Jérémie; Busa, Tiffany; Germain, Dominique; Nadeau, Gwenaël; Puechberty, Jacques; Coubes, Christine; Gatinois, Vincent; Cacciagli, Pierre; Duffourd, Yannis; Pinard, Jean-Marc; Tevissen, Hélène; Villard, Laurent; et al.
Abstract Introduction A large number of genes involved in autosomal recessive forms of intellectual disability (ID) were identified over the past few years through whole-exome sequencing (WES) or whole-genome sequencing in consanguineous families. Disease-associated variants inTRAPPC9 were reported in eight multiplex consanguineous sibships from different ethnic backgrounds, and led to the delineation of the phenotype. Affected patients have microcephaly, obesity, normal motor development, severe ID, and language impairment and brain anomalies. Patients We report six new patients recruited through a national collaborative network. Results In the two patients heterozygous for a copy-number variation (CNV), the phenotype was clinically relevant with regard to the literature, which prompted to sequence the second allele, leading to identification of disease-associated variants in both. The third patient was homozygote for an intragenicTRAPPC9 CNV. The phenotype of the patients reported was concordant with the literature. Recent reports emphasized the role of CNVs in the etiology of rare recessive disorders. Conclusion This study demonstrates that CNVs significantly contribute to the mutational spectrum ofTRAPPC9 gene, and also confirms the interest of combining WES with CNV analysis to provide a molecular diagnosis to patients with rare Mendelian disorders.